2019
DOI: 10.12688/hrbopenres.12914.1
|View full text |Cite
|
Sign up to set email alerts
|

Myopia Outcome Study of Atropine in Children (MOSAIC): an investigator-led, double-masked, placebo-controlled, randomised clinical trial protocol

Abstract: The Myopia Outcome Study of Atropine in Children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…According to the Ministry of Health and Welfare of Taiwan, more than 80% of all school children develop myopia by the end of high school in Taiwan [ 5 ]. Since the increase in myopia cases is a worldwide trend, there are many effective mechanisms to control myopia progression such as atropine [ 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], orthokeratology [ 19 , 20 ], experimental bifocal/multifocal soft contact lenses (CLs) [ 21 , 22 ], commercial bifocal or multifocal soft CLs dedicated to presbyopia corrections but used for myopia control [ 23 , 24 ], and commercial multifocal CLs specially dedicated to myopia control [ 25 , 26 ]. Atropine, an anticholinergic blocking agent, can temporarily paralyze the smooth ciliary muscle causing cycloplegia.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Ministry of Health and Welfare of Taiwan, more than 80% of all school children develop myopia by the end of high school in Taiwan [ 5 ]. Since the increase in myopia cases is a worldwide trend, there are many effective mechanisms to control myopia progression such as atropine [ 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], orthokeratology [ 19 , 20 ], experimental bifocal/multifocal soft contact lenses (CLs) [ 21 , 22 ], commercial bifocal or multifocal soft CLs dedicated to presbyopia corrections but used for myopia control [ 23 , 24 ], and commercial multifocal CLs specially dedicated to myopia control [ 25 , 26 ]. Atropine, an anticholinergic blocking agent, can temporarily paralyze the smooth ciliary muscle causing cycloplegia.…”
Section: Introductionmentioning
confidence: 99%
“…A range of optical and pharmacological interventions, such as atropine eye drops (at varying concentrations), multifocal contact lenses, orthokeratology and defocus modifying spectacle lenses (DIMS) have been demonstrated to reduce myopia progression when compared with single vision spectacle lenses or placebo [12][13][14] . Studies have also indicated bifocal and progressive addition spectacle lenses can also slow the progression of myopia in children with near-point esophoria and larger accommodative lags [15][16][17] . Low dose atropine is not readily available as a licensed product in Europe but is accessible through clinical trials, with the recruitment of trial participants dependent on Optometrist referrals [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances, the majority of progressive myopes are still prescribed single vision spectacles, especially in countries outside of Asia [13][14][15] . There is a scarcity of published literature that examines the possible reasons for the very limited uptake of active myopia management.…”
Section: Introductionmentioning
confidence: 99%
“…There is a scarcity of published literature that examines the possible reasons for the very limited uptake of active myopia management. A search of various databases including MEDLINE, EMBASE, Google Scholar, Scopus, the World Health Organization International Clinical Trials Registry Platform, and ClinicalTrials.gov during the preparatory stages of this study revealed only three research papers and a round table discussion that explored the knowledge and attitudes of eye care professionals toward myopia and its control [13][14][15][16] . Rather than a lack of evidence for efficacy, the barriers appear largely attitudinal; eye-care practitioners consider the information required to implement myopia control techniques to be lacking, as well as reporting concerns about the safety, cost and availability of such measures 13 .…”
Section: Introductionmentioning
confidence: 99%